Enhancement Assessment of Legal Law and Protection A Regional Culture - Dina Andiza (Budapest International Research and Critics University, 2022)
This Study discussed about traditional knowledge (PT) and traditional cultural expressions (EBT) is a state asset that is very potential for prosperity nation because it has high economic value, but ownership many recognized (claimed) by foreign parties without any benefit sharing, resulting in a conflict of interest between developed countries and the state developing like Indonesia. Our weakness in developing the protection system there is no proper protection system and adequate and limited data, documentation and information about PT and EBT. The struggle of Indonesia as one of the developing countries for legal protection to continue form a proper protection system for traditional knowledge at the international level in 2000 IGC-GRTKF was formed (Intergovernmental Committee on Genetic Resources, Traditional Knowledge, and Folklor) by WIPO to discuss the possibility of holding a binding agreement, in an effort the law to protect internationally, then at the national level The government is conducting a discussion on the Draft Law (RUU) concerning SDGPTEF (Genetic Resources, Traditional Knowledge and Expression of Traditional Culture. While which already exists, namely Law Number 19 of 2002 concerning Rights Cipta is not fully operational, because there is no regulation Implementation.